STUDY OF THE ANTIDEPRESSANT ACTIVITY OF FOLIC ACID AND VITAMIN-D ON RESERPINE INDUCED DEPRESSION IN MICE. - L, Borah; M, Lahkar; S, Dasgupta (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Low levels of folic acid and deficiency of Vitamin D have been found to be associated with poor mood and depression. This study was designed to investigate whether these vitamins show antidepressant activity in models of depression in mice. Methods: Reserpine was used to induce depression in the study groups. Low and high doses of folic acid and Vitamin D as well as combinations of these vitamins in low and high doses were administered after induction of depression. The test animals were then tested on forced swim test, tail suspension test, and open field test models for evaluation of the antidepressant activity. Results: After 2 weeks of drug treatment, all the treated groups showed a significant reduction in immobility time in both the test models (p<0.05). High dose folic acid showed consistently greater antidepressant property in all the test models throughout the study period. High dose Vitamin D (p<0.05) also showed good antidepressant activity after 2 weeks, the delayed antidepressant effect of which might be attributable to the molecular mechanism of action of Vitamin D. Conclusion: Our study demonstrates that both folic acid and Vitamin D have antidepressant activity. The antidepressant activity of high dose folic acid (50 mg/kg) in reserpine-induced depression in mice at the end of 2 weeks was more pronounced in our study. Studies with longer duration of treatment are warranted to further evaluate their antidepressant effect.